Pigeon Farming In Gouripur Upazilla Of Mymensingh District - Asaduzzaman, M; Mahiuddin, M; Howlider, MAR; Hossain, MM; Yeasmin, T (Bangladesh Journal of Animal Science, 2012)
A survey was conducted using a pre-tested interview schedule in the village Charnelukhia under Gouiripur upazilla of Mymensingh district to study the present status, problems and prospects of pigeon farming in the rural areas of Bangladesh. Data were collected from 15 pigeon farmers. Housing cost, height of house, duration of house, quantity of feed supplied to each pigeon/day, male female ratio, marketing age, weight, price of squab, number of squab/pair of pigeon, production of squab/year/pair of pigeon, price of each pigeon and mortality of pigeon were Tk. 113.33, 3.50m, 5 years, 34.50g, 1.07, 26.66 days, 258g, Tk. 51, 1.67, 19.53, Tk. 113.33 and 6.67% respectively. Most of the pigeon farmers rear pigeon in small scale scavenging system with supplementary feeding. They have no idea about breed and variety of pigeon and prevention of diseases. There is a lot of demand of squab meat in the market due to its delicacy and taste. The pigeon farming may be increased with government initiative providing training to farmers and extending loans. Introduction of meat breeds, good flock size and balanced feed need to be ensured for improving income and employment opportunity. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9923 BJAS 2009; 38(1-2): 142-150